Optical Studies of Er-doped Yttrium Aluminium Garnet Phosphor Materials - N. Norhashim; S. Kaveh; A. K. Cheetham; R. J. Curry (IAES Indonesia Section, 2019)
The need for materials application in solid-state lasers, medical devices, and optoelectronic devices has made the investigation of ceramic materials of increasing importance. A detail study of the optical properties of rare earth element typically from luminescent materials when intentionally doped inside the host materials and in particular crystal (such as YAG) is reported for the photoluminescence, power and lifetime measurement. The rare-earth dopants usually form trivalent lanthanide ions and the energy transfer and optical transitions involved originate from 4f-4f transitions of the ions and between these states and the host material. In order to understand the energy transfer processes in more detail we need to better understand the accompanying optical processes that give rise to the emission they display and it is this that forms the focus of the work presented. Following this second (and higher) order processes are considered that lead to upconversion in erbium-doped yttrium aluminum garnet (Er:YAG) materials.